АСПЕКТЫ КОРРЕКЦИИ ДИСФУНКЦИ ЭНДОТЕЛИЯ ПРИ ИШЕМИЧЕСКОМ ИНСУЛЬТЕ - И. Н. Каграманян; А. Ю. Малыгин; А. Л. Хохлов; О. Н. Курочкина (Архивъ внутренней медицины, 2013)
Simvastatin 40 mg/day prescribed with neuroprotective and antihypertensive treatment in acute stage of ischemic stroke leads to lowering of recurrent cardiovascular events number, positive dynamics of neurological status, regression of endothelial dysfunction, associated with improved renal function.